POSITIVE AND NEGATIVE PSYCHOLOGICAL CORRELATES, GENDER SPECIFIC AND TRADITIONAL FACTORS FOR FIRST ONSET ANGINA IN A SAMPLE OF PAKISTANI WOMEN - Rafique, Rafia; Anjum, Afifa (Journal of Ayub Medical College Abbottabad, 2015)
Background: Coronary Heart Disease (CHD) occurs to a greater extent in developed than developing countries like Pakistan. Our understanding of risk factors leading to this disease in women, are largely derived from studies carried out on samples obtained from developed countries. Since prevalence of CHD in Pakistan is growing, it seems pertinent to infer risk and protective factors prevalent within the Pakistani women. This case control study investigated the role of psychological, traditional and gender specific risk and protective factors for Angina in a sample of Pakistani women aged between 35-65 years. Methods: Female patients admitted with first episode of Angina fulfilling the study inclusion/exclusion criteria were recruited within the first three days of stay in the hospital. One control per case matched on age was recruited. Translated versions of standardized tools: Life Orientation Test (LOT), The Hope Scale, Subjective Happiness Scale and Depression, Anxiety and Stress Scale (DASS) were used to measure the psychological variables. Information on medical conditions like diabetes, hypertension, family history of IHD, presence and absence of menopause and use of oral contraceptive pills was obtained from the participants. Body Mass Index for cases and controls was calculated separately with the help of height and weight recorded for the participants. Results: Multivariate logistic regression analyses revealed that depression, anxiety and stress are risk factors, were as optimism and hope are protective predictors of Angina. 64% and 85 % of variance in Angina were attributed to psychological factors. Menopause, diabetes and hypertension are significantly associated with the risk of Angina, explaining 37% and 49 % of variance in Angina. The study provides evidence for implementation of gender specific risk assessment and preventive strategies for Angina. The study gives directions for large scale prospective, epidemiological, longitudinal as well as interventional studies, to be tailored for indigenous population and secondly development and standardization of measures to appraise psychological factors of Angina prevalent within the Pakistani population